EXAMPLES OF DIGITAL VERSIONS OF THE CRAO SPECTRAL PHOTOGRAPHIC ARCHIVES - Gorbunov, M.; Shlyapnikov, A. (Одеські астрономічні публікації, 2013)
The glass library of Crimean Astrophysical Observatory (CrAO) comprises of about 15,000 photoplates and films with the spectra of planets, stellar, nebula and extragalactic objects. All spectra were obtained in period from 1929 to 1990 years and separated on different collections. Some results of the digitizing photoplates from these collections are presented in this paper.